Family resilience and childhood obesity among children exposed to adverse childhood experiences in a national survey - William J. Heerman; Lauren R. Samuels; Tavia González Peña; Chelsea vanWyk; Lindsay S. Mayberry; Julie Lounds Taylor; Nina C. Martin (Wiley, 2022)
Abstract Objective Adverse childhood experiences (ACEs) contribute to poor overall health among children with obesity. This study evaluated how one potential protective factor-family resilience-affects the association between ACEs and childhood obesity. Methods This analysis was a secondary analysis of the 2016-2018 National Survey of Children's Health (NSCH), a repeated cross‐sectional survey based on parent report. Nine ACEs were queried. Family resilience was assessed with four items (potential range 0-12). The primary outcome was child weight status. Multivariable ordinal logistic regression was used, adjusting for potential confounders and the interaction between ACEs and family resilience. Results For 49,365 children ages 10-17, the median number of ACEs was 1 (IQR 0, 2), the median family resilience score was 10 (IQR 8,12), 15.3% of children had overweight, and 15.4% of children had obesity. Among the 51.3% of children who experienced one or more ACEs, higher family resilience scores attenuated the odds of being in a higher weight category. This pattern was not observed in children with zero ACEs. Conclusions In the 2016-2018 NSCH, children ages 10-17 who were exposed to ACEs had higher rates of overweight and obesity, the odds of which may be reduced when children also have higher family resilience.